Localization of a portion of an endorectal balloon for prostate image-guided radiation therapy using cone-beam tomosynthesis: a feasibility study - Ng, Sook Kien (International journal of radiation oncology, biology, physics, 2012)
Purpose: To assess the feasibility of using cone-beam tomosynthesis (CBTS) to localize the air-tissue interface for the application of prostate image-guided radiation therapy using an endorectal balloon for immobilization and localization. Methods and Materials: A Feldkamp-David-Kress-based CBTS reconstruction was applied to selected sets of cone-beam computed tomography (CBCT) projection data to simulate volumetric imaging achievable from tomosynthesis for a limited range of scan angles. Projection data were calculated from planning CT images of 10 prostate cancer patients treated with an endorectal balloon, as were experimental CBCT projections for a pelvic phantom in two patients. More than 50 points at the air-tissue interface were objectively identified by an intensity-based interface-finding algorithm. Using three-dimensional point sets extracted from CBTS images compared with points extracted from corresponding CBCT images, the relative shift resulting from a reduced scan angle was determined. Because the CBCT and CBTS images were generated from the same projection data set, shift identified was presumed to be due to distortions introduced by the tomosynthesis technique. Results: Scans of ≥60° were shown to be able to localize an air-tissue interface near the isocenter with accuracy on the order of a millimeter. The accuracy was quantified in terms of the mean discrepancy as a function of reconstruction angle. Conclusion: This work provides an understanding of the effect of scan angle used in localization of a portion of an endorectal balloon by means of CBTS. CBTS with relatively small scan angles is capable of accurately localizing an extended interface near the isocenter and may provide clinically relevant measurements to guide IGRT treatments while reducing imaging radiation to the patient.